Diversity of nitrate, oxalate, vitamin C and carotenoid contents in different spinach accessions and their correlation with various morphological traits. Issue 4 (4th July 2018) - Wang, Xiaoli; Cai, Xiaofeng; Xu, Chengxi; Zhao, Qi; Ge, Chenhui; Dai, Shaojun; Wang, Quan-hua
ABSTRACT: Spinach ( Spinacia oleracea L.) accumulates high amounts of carotenoids, vitamin C, nitrate and oxalate. Breeding to reduce nitrate and oxalate levels and increase vitamin C and carotenoid levels is a major target in spinach nutritional quality improvement. Here we investigate natural variations in the levels of nitrate, oxalate, vitamin C, and total carotenoid in 98 spinach accessions, and correlations among these four nutritional components and 12 important morphological traits. Our results showed that the concentrations of nitrate, oxalate, vitamin C, and total carotenoid ranged from 0.21–3.83, 2.38–34.72, 0.51–1.30, and 0.18–0.58 mg g −1 fresh weight (FW), respectively. Moderate positive correlations were observed between the levels of oxalate and vitamin C, and between vitamin C and total carotenoid, whereas the levels of nitrate were correlated weakly and negatively with those of vitamin C and total carotenoid. The nitrate contents of crinkle-leaf accessions were significant higher than those of smooth-leaf accessions, and the smooth-leaf accessions had significantly higher concentrations of oxalate and vitamin C than crinkle-leaf accessions. Furthermore, hierarchical clustering analysis identified eight spinach accessions that could be served as starting materials for breeding new spinach cultivars with increased levels of vitamin C and carotenoids and simultaneously decreased accumulation of nitrate and oxalate.